The Grapevine (London : Video Arts, 1991)
Keeping everyone informed of what is happening in an organisation and while it may be time consuming, but the alternative is speculation and rumour, and that can be extremely costly
Bibliographical information is taken from publisher's catalogue
Keywords: Communication in management